Seasonal and circadian rhythms of clerodane diterpenes and glycosylated flavonoids in two varieties of Casearia sylvestris Sw. (Salicaceae) - Paula C.P. Bueno; Gabriel S. Viana; Livia L. Thomaz; Daniela A. Chagas-Paula; Michael Hippler; Alberto J. Cavalheiro (Heliyon)
Casearia sylvestris Sw. (Salicaceae) is noted for its morphological and chemical plasticity and pharmacological properties. The present study investigates two of its varieties: C. sylvestris var. sylvestris, predominant in dense and humid forests and ecotones and characterized by clerodane diterpenes; and C. sylvestris var. lingua, mainly found in xeric and open savannah areas and containing phenolic compounds. Despite their comprehensive chemical profiles, the dynamics of clerodane diterpenes and glycosylated flavonoids remain unknown. This study thus aimed to describe seasonal and circadian variations in their content in the leaves of the two varieties. The relative contents of five diterpenes and three glycosylated flavonoids were monitored monthly, every 3 h for 48 h, over 1 year via high-performance liquid chromatography coupled to diode array detection (HPLC-UV-DAD). The differential expression of photosynthetic proteins (Rubisco and photosystem II) was analyzed by Western blotting. The contents of both chemical classes decreased during the reproductive stage, though the prevalence of diterpenes in var. sylvestris and flavonoids in var. lingua remained unchanged; furthermore, even when the plants are grown under the same geographic and environmental conditions, Rubisco expression in var. lingua is twice that of var. sylvestris. In var. lingua, photosystem II proteins are 10 % less expressed. The study reveals the circadian and seasonal fluctuations and, thus, prevalence of the two main compound classes in the examined varieties. The expression of the investigated photosynthetic proteins provides insights into the two varieties, supporting the prevalence of var. lingua in Cerrado areas and var. sylvestris in Atlantic Forest areas.